Pharmacokinetics, Safety, and Tolerability of Once‐Daily Intranasal Fluticasone Furoate and Levocabastine Administered Alone or Simultaneously as fluticasone Furoate/Levocabastine Fixed‐Dose Combination. Issue 3 (4th December 2015) - Allen, Ann; Murdoch, Robert D.; Bareille, Philippe; Burns, Olivia; Hughes, Stephen; Gupta, Ashutosh; Miller, Sam R.
Abstract: Purpose: The purpose of this study was to investigate potential systemic pharmacokinetic interactions between intranasal fluticasone furoate (FF) and levocabastine (LEVO) when delivered simultaneously via a metered atomizing spray pump. Methods: This was a randomized, open‐label, crossover study. Healthy male and female subjects (n = 30) received once‐daily repeat doses of FF/LEVO (100/200 μg) as a fixed‐dose combination (FDC), FF (110 μg), or LEVO (200 μg) for 7 days. FF and LEVO plasma pharmacokinetics (0–24 hours) were measured on day 7, with safety assessments over the study duration. Results: Systemic exposure to LEVO was similar when administered as FF/LEVO FDC or LEVO alone. Following FF/LEVO FDC or FF alone, the majority (>99%) of FF concentrations were nonquantifiable, that is, below the lower limit of quantification of 10 pg/mL. All treatments were well tolerated, and adverse event incidence was similar across the treatment groups. Conclusions: These results suggest that in healthy subjects, for LEVO, there is no pharmacokinetic interaction with FF when delivered as FF/LEVO FDC. As the majority of data were below the assay sensitivity for FF, any potential differences in the bioavailability of FF when delivered alone or as FF/LEVO FDC could not be established. There was no clinically relevant impact on safety/tolerability when FF/LEVO was coadministered.